Perceptions of Pregnant Mothers in Stimulating the Fetus - Nuraina Nuraina; Tri Sunarsih; Dhesi Ari Astuti (GLOBAL HEALTH SCIENCE GROUP, 2022)
Fetal stimulation is an attempt made by parents to stimulate the fetus to increase its fundamental abilities so that it can grow and develop properly after birth. Fetal stimulation is in keeping with the government's First 1000 Days of Life program, which states that from the time the baby is formed in the womb until the kid is 2 (two) years old, there is an accelerated phase of growth and development. This study aimed to ascertain pregnant women's perceptions of stimulating the fetus. As there are still many pregnant women who don't know how to properly stimulate the fetus, this type of research is still uncommon but highly intriguing to examine. A qualitative research method with a phenomenological perspective was employed in this study. 15 pregnant ladies were interviewed in-depth and their conversations were recorded on audio files. employing a system of purposeful sampling to find informants. This study's analysis was conducted using NVivo 12 Plus. The study's findings focused on two themes: how to comprehend fetal stimulation and how gestational age affects fetal stimulation. The mother's comprehension of and gestational age in stimulating the fetus affects the mother's impression of stimulating the fetus. For pregnant women's perceptions of fetus stimulation, the majority of moms already know how to stimulate the fetus, notably through caressing, conversing, reading the Qur’an, and listening to murottal and music. However, there are still women who are unaware of fetal stimulation. The sort of fetal stimulation was administered by pregnant women at the same time in this study, thus it was not committed to specific forms of stimulation.